Implementation of Contextual Learning Based on Lesson Study Model - Titis Angga Rini (Faculty of Education Universitas Negeri Malang, 2020)
This study aims to improve student achievement and activities in library management courses at the elementary teacher education study program. As practical learning, contextual learning will be implemented involving activities of surveys and practicum. This research used a qualitative approach with action research based on lesson study design in the cycles of plan, do, and see. Results of the first and second cycle showed that student achievement under contextual learning model increased. This was assessed through test scores obtained by the students.